Chemical regulation of growth and fruit maturity of Vitis vinifera 'Flame Seedless' using hydrogen cyanamide - Mayles, Karen Marie, 1957- (The University of Arizona., 1987)
The effect of hydrogen cyanamide (H₂CN₂) on budbreak and fruit maturity of 2-year old 'Flame Seedless' table grapes was investigated in a low desert climate in central Arizona. Dormant sprays of H₂CN₂ applied at 2.5 and 5.0% (v/v) concentrations hastened budbreak by at least 16 days with subsequent advancement of fruit maturity by 5 to 10 days. A 5.0% (v/v) dormant application of H₂CN₂ to whole vine, buds only or pruning cuts only advanced budbreak by at least 16 days and advanced fruit maturity by 1 to 5 days, regardless of application site. A more uniform budbreak was observed on H₂CN₂ treated vines, regardless of concentration or site of application when compared to control vines.